PENERAPAN RISK BASED AUDIT UNTUK MENINGKATKAN EFISIENSI DAN EFEKTIVITAS PROSES OPERASIONAL UD.X - Feliciana Allice Sasmita; Yenny Sugiarti (Perpustakaan Universitas Surabaya, 2018)
The purpose of this research is to assess the risk and effectiveness of internal controls that have been applied to building materials supplier ‘UD.X’ in Surabaya. Auditor used risk based audit approach to focus on high risk areas and reduce the impact and likelihood of those risks to acceptable level. Auditor found significant findings in the risk of out of stock inventory, unorganized warehouse, difference quantity between stock opname and inventory stock data, misinterpretation of sales price, delivery delay to customers, and the overdue of customers’ payment. Auditor recommends UD.X to evaluate sales trend so UD.X can anticipate customers’ order, organize the warehouse based on priorities, improve monitoring’s function of storing process, give the responsibility of setting the price to a dependable person, make sure the processed documents and unprocessed documents are separated, and remind the customers 3 days before deadline due payment. Thus the recommendation can improve the effectiveness, efficiency, and economics of the internal controls applied.